Women’s posttraumatic stress symptoms and autism spectrum disorder in their children - Roberts, Andrea L. (2014)
Maternal posttraumatic stress disorder (PTSD) may be associated with autism spectrum disorder (ASD) in offspring through multiple pathways: maternal stress may affect the fetus; ASD in children may increase risk of PTSD in mothers; and the two disorders may share genetic risk. Understanding whether maternal PTSD is associated with child’s ASD is important for clinicians treating children with ASD, as PTSD in parents is associated with poorer family functioning. We examined the association of maternal PTSD with offspring ASD in a large US cohort (N ASD cases = 413, N controls = 42,868). Mother’s PTSD symptoms were strongly associated with child’s ASD (RR 4-5 PTSD symptoms=1.98, 95% CI=1.39, 2.81; RR 6-7 symptoms=2.89, 95% CI=2.00, 4.18). Clinicians treating persons with ASD should be aware of elevated risk of PTSD in the mother. Genetic studies should investigate PTSD risk alleles in relation to ASD.